Identification of Termite House Cementation as an Effort to Make Synthetic Cementation for Soil Conservation - Angga Prasetya; Sri Nuryani Hidayah Utami (The University of Lampung, 2023)
Termites are social insects that have strong and hard nests. The purpose of this study was to identify the cementation material for termite nests which makes termite nests sturdy so they are resistant to rain or erosion. Sampling was carried out by random sampling method in three different districts, namely Gunung Kidul, Kulon Progo and Bantul. Parameters observed for the identification of cementation materials were pH, C-organic, organic matter, texture, protein and fat. In general, the parameters in the termite nest have a higher value than the soil around the termite nest. C-organic termite nests in Gunung Kidul by 2.82%, Kulon Progo 3.05% and Bantul 3.46%. While the organic matter content in the soil of Gunung Kidul is 2.06%, Kulon Progo is 2.21% and Bantul is 3.00%. The protein content in termite mounds is 0.17% in Gunung Kidul, 0.19% in Kulon Progo, and 0.15% in Bantul. The protein content in the soil around the nests was 0.10% in Gunung Kidul, 0.12% in Kulon Progo and 0.10% in Bantul. The texture of the termite nest and the soil around the nest is loamy and loamy loam. Based on the results of the analysis obtained, the construction of termite nests is dominated by clay material with adhesive or cementation of organic matter and protein produced from termite saliva. Soil conservation can be done by adding organic matter and protein to stabilize and strengthen soil aggregates. Keywords : Clay, Protein, Termite, Soil Conservation